PENDAMPINGAN SOSIAL-EMOSIONAL ANAK USIA DINI MELALUI PENDEKATAN BIMBINGAN KONSELING ISLAM DI RA ASSAKINAH BATAM - Rahmi Aulia, Arinda; Afrizawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Early childhood education is a crucial stage in the formation of character, social development, and children's readiness to learn. At this stage, children experience a period known as the golden age, during which they require appropriate guidance to support optimal emotional and social development. This study aims to describe the process of social-emotional guidance for early childhood through the Islamic Guidance and Counseling approach at RA Assakinah Batam. This research employed a descriptive qualitative approach. Data were collected through observation, participation in learning activities, and reflection during the implementation of the School Field Introduction (PLP) program. The results show that social-emotional guidance for children is implemented through the cultivation of Islamic values, gentle communication, educational play activities, and a personal approach for children who experience difficulties in adapting to the school environment. In addition, educators apply enjoyable learning methods such as singing, storytelling, and creative activities to foster children's self-confidence and social skills. The application of Islamic Guidance and Counseling in early childhood education contributes to the development of discipline, independence, and the ability to interact positively with peers. Therefore, the Islamic Guidance and Counseling approach plays an important role in supporting the optimal social and emotional development of children.